PENGARUH PEMBERIAN OKSIGEN DAN ELEVASI KEPALA 30º TERHADAP TINGKAT KESADARAN PADA PASIEN CEDERA KEPALA SEDANG - Luci Riani Ginting; Kuat Sitepu; Renni Ariana Ginting (Fakultas Keperawatan dan Fisioterapi Institut Kesehatan Medistra Lubuk Pakam, 2020)
Head injury is directly or indirectly mechanical injuries that resulted wound in the scalp, skull fracture, tear the lining of the brain, and brain damage, and neurological disorders. The basic method for brain protection of head injury patients are freeing the airway and giving adequate oxygenation. Giving oxygen and headv elevation 30° of head are the appropriate action for the moderate head injury classification to launch the cerebral oxygen perfusion and to increase consciousness level. The purpose of this research were to determine the GCS before and after giving oxygenation with and position 30 ° of head and to analyze the effect of giving oxygen and headv elevation30 °of head to change the levels of consciousness of moderate head injury patients. This research was an Quasi-Experimental study with 10 respondents. The test were used Paired Sample T-test Test. The results showed that there was an effect of giving oxygen and headv elevation 30 °of head toward to change the level of consciousness of moderate head injury patients. GCS average value before was 10.10 and GCS average after 12.90 value was with p value was 0.000. Keywords : Levels of Consciousness GCS, Moderate Head Injury, Position 30° of the Head